Biological Networks: An Introductory Review - Saad Zaghloul Salem Mohammad (Journal of Proteomics and Genomics Research, 2018)
All aspects of life activities in living cells are mediated/executed and regulated by a vast number of networks, comprising a wide spectrum of components, starting with simple biomolecules and ending with the whole organism, and functioning within a precisely organized tight framework. Proper mediation of cellular activities necessitates their inclusion within the context of structured and organized network systems capable of regulating/coordinating and synchronizing the countless numbers of biological processes occurring within living cells. The number of biological networks and pathways within the living cell is considerably huge, being dependent on the structural complexity and functional capabilities of the cell. Pathogenesis and progression of human diseases result from functional disturbances of biological networks within the cell as disturbed network function leads to deleterious effects on physiological processes dependent on, and mediated by, affected network(s). Ensuing pathological processes, defined by the nature of disturbed networks and the specific organs or tissues affected, pave the way for the development of pathognomonic and characteristic disease entities. As most network functions are dependent on relatively small number of key regulatory biomolecules, i.e. enzymes/proteins and signal transducing factors, it follows that functional disturbances of biological networks and pathogenesis of disease states can be attributed, in most instances, to quantitative and/or qualitative abnormalities of these key regulatory molecules. Study and analysis of the structural designs and the functional mechanisms of biological networks would have crucial and important impacts on many theoretical and applied aspects of biology, in general, and of medical sciences in particular. Meticulous study of biological networks represents an important and integral aspect in study of biology. Interpretation and analysis of key information deduced from observing and analyzing structural designs and functional characteristics and dynamics of biological networks discloses and defines the basic framework within which life activities in living cells are initiated, adapted to physiological requirements, maintained, and terminated upon completion of their aims. More important, however, is the contribution of this information to proper understanding of the different mechanisms responsible for regulating and synchronizing the functions and performances of the vast spectrum of different network categories within the cell. In addition to its vital scientific significance, discovering and defining the key pivotal structural and regulatory molecules within life-mediating networks, and along different pathways responsible for controlling functional dynamics of the network, represent an indispensable diagnostic approach insistent for designing proper therapeutic approaches to diseases caused by network defects.
Keywords: Biological networks